Economic analysis, moral philosophy, and public policy - Hausman, Daniel M. (New York Cambridge University Press, 2006)
This 2006 book shows through accessible argument and numerous examples how understanding moral philosophy can improve economic analysis, how moral philosophy can benefit from economists' analytical tools, and how economic analysis and moral philosophy together can inform public policy. Part I explores rationality and its connections to morality. It argues that in defending their model of rationality, mainstream economists implicitly espouse contestable moral principles. Part II concerns welfare, utilitarianism and standard welfare economics, while Part III considers important moral notions that are left out of standard welfare economics, such as freedom, rights, equality, and justice. Part III also emphasizes the variety of moral considerations that are relevant to evaluating policies. Part IV then introduces technical work in social choice theory and game theory that is guided by ethical concepts and relevant to moral theorizing. Chapters include recommended readings and the book includes a glossary of relevant terms.
Includes bibliographical references (p. 315-333) and index.
Keywords: Economics--Moral and ethical aspects